Análise estrutural metabólica de neurônicos da amígdala basolateral de ratos wistar submetidos ao protocolo de estresse pós-traumático - Neves, Laura Tartari (2019)
Amygdala is one of the main regions involved in posttraumatic stress disorder (PTSD) and plays an important role in the neuronal circuits for fear and anxiety and emotional reactivities. Previous imaging research reported abnormal amygdala function in patients with PTSD. In addition, alterations in synaptic plasticity have been associated with psychiatric disorders and previous reports have indicated alterations in the amygdala morphology, especially in basolateral (BLA) neurons, are related to fear and anxiety in animal models of stress-related disorders. Since, some individuals exposed to a traumatic event develop PTSD, the goals of this study were to evaluate the early effects of PTSD on amygdala glucose metabolism and analyze the possible BLA dendritic spine plasticity in animals with different levels of behavioral response. We employed the inescapable footshock protocol as an experimental model of PTSD and the animals were classified according to the duration of their freezing behavior into distinct groups: “extreme behavioral response” (EBR) and “minimal behavioral response” (MBR). We evaluated the amygdala glucose metabolism at baseline (before the stress protocol) and immediately after the situational reminder using the microPET-CT and 18F-FDG. The BLA dendritic spines were analyzed according to their number, density, shape, morphology and quantitative parameters related to the spine length (SL), neck length (NL), head diameter (HD) and neck diameter (ND) in the same population. Our results show that animals classified as EBR exhibited longer freezing behavior and an increase in the proximal spine density of BLA neurons. Amygdala glucose metabolism, dendritic morphology and morphometric parameters showed no significant differences. Our results show that the extreme behavior response induced by this PTSD protocol can induce an early increase in BLA spine density, which is unassociated with either morphological changes in spines or metabolic changes in amygdala in Wistar rats.